2021
DOI: 10.2147/ijgm.s333751
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Non-COVID-19 Community-Acquired Pneumonia in COVID-19 Pandemic

Abstract: Introduction:The COVID-19 lockdown strategies were associated with a significant decrease in infectious diseases disseminated through airborne or fecal-oral transmissions. Social distancing and other lockdown strategies effectively slowed down the spread of common respiratory viral diseases and decreased the need for hospitalization among children. Thus, a decline in the incidence of respiratory viral diseases had been reported following the COVID-19 outbreak. However, the trend of non-COVID-19 pneumonia in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These decreases are clearly explained by the decrease in bacterial respiratory infections during the pandemic. Other authors found the same phenomenon, attributing the drop in respiratory infections (not COVID-19 infections) during the pandemic to social distancing (for example, schools closing), the use of face masks, decreased visits to doctors’ offices and emergency services, and measures of more restrictive health protocols during the pandemic ( Kuitunen et al, 2020a ; Kuitunen et al, 2020b ; Chiapinotto et al, 2021 ; Huang, 2021 ). All these measures contributed to the decrease in the transmissibility of respiratory pathogens, with a consequent decrease in the number of infections and use of these antibiotics.…”
Section: Discussionmentioning
confidence: 79%
“…These decreases are clearly explained by the decrease in bacterial respiratory infections during the pandemic. Other authors found the same phenomenon, attributing the drop in respiratory infections (not COVID-19 infections) during the pandemic to social distancing (for example, schools closing), the use of face masks, decreased visits to doctors’ offices and emergency services, and measures of more restrictive health protocols during the pandemic ( Kuitunen et al, 2020a ; Kuitunen et al, 2020b ; Chiapinotto et al, 2021 ; Huang, 2021 ). All these measures contributed to the decrease in the transmissibility of respiratory pathogens, with a consequent decrease in the number of infections and use of these antibiotics.…”
Section: Discussionmentioning
confidence: 79%
“…During the COVID-19 pandemic, CAP decreased by 72.3% [ 27 ]. It turns out that interventions for controlling COVID-19 (prevention of droplet transmission and direct contact) could prevent seasonal influenza and CAP [ 28 ]. Study results in adult patients showed that elderly pneumonia cases decreased in hospitals that did not accept COVID-19 patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the wearing of masks was widely recommended throughout the city in all instances of close person-to-person contact, and children and adolescents were asked to wash their hands frequently at kindergartens and schools. Huang showed that the strategy to prevent the outbreak of COVID-19 was also effective at preventing pediatric CAP in Taiwan where the number of pediatric patients with CAP decreased by an average of 72.3% in 1 year (15). Yamamoto reported a similar situation among adults; that is, the number of patients with CAP began to decrease in February 2020, and was significantly lower than those from the same period for the last 3 years ( 16).…”
Section: Discussionmentioning
confidence: 99%